2003
DOI: 10.1108/02621710310474750
|View full text |Cite
|
Sign up to set email alerts
|

A cross method analysis of the impact of culture and communications upon a health care merger

Abstract: The incidence of mergers and acquisitions has proliferated throughout the world including all sectors of our society, both municipal and industrial, private and public. However, the majority (60-80 percent) of them do not reach their intended objectives owing to the fact that the merging organizations do not realize the impact of neglecting the human resource factor. Although they properly assess and address the financial and legal issues, they continually overlook this critical factor. The present literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Moreover, the authors also found that both organizational and national cultural differences are positively associated with knowledge transfer. However, rather strikingly, Appelbaum and Gandell (2003) underlined the fact that actively managing cultural differences during all stages of a merger reduces cultural clash in M&A. Weber et al (1996) found that in the context of international M&As, national culture differentials are better predictors of stress and negative attitudes toward the merger than organizational (corporate) culture differentials.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors also found that both organizational and national cultural differences are positively associated with knowledge transfer. However, rather strikingly, Appelbaum and Gandell (2003) underlined the fact that actively managing cultural differences during all stages of a merger reduces cultural clash in M&A. Weber et al (1996) found that in the context of international M&As, national culture differentials are better predictors of stress and negative attitudes toward the merger than organizational (corporate) culture differentials.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…However, the loss of autonomy during high-level integration that generally is necessary to reap the synergistic benefits can have an adverse impact on M&A performance (Chatterjee et al, 1992; Haspeslagh & Jemison, 1991; Puranam et al, 2006). Appelbaum and Gandell (2003) found that actively managing cultural differences during all stages of a merger minimizes cultural clash in M&A. Weber et al (2011) showed on their part that the positive effect of synergy potential and negative effect of cultural differences are moderated through the appropriate integration approach (symbiosis) to create high integration effectiveness.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Strategic management scholars believed that M&A is a means to diversification (Ansoff et al, 1971;Dixon et al, 2001;Walter and Barney, 1990), economists concerned about the economic motives of M&A (Goldberg, 1983;Holder, 1993), finance scholars examined M&A performance from stockmarket-based measures (Jarrell et al, 1988;Jensen and Ruback, 1983;Ramaswamy and Waegelein, 2003), organization theorists emphasized the management of the post-acquisition integration process (Bijlsma-Frankema, 2001;Haspeslagh and Jemison, 1991), and human resource scholars focused on effective human resource systems and communication (Applebaum and Gandell, 2003;Levinson, 1970). Yet, comparatively little is known about the effects of business ethics on the success or failure of M&A.…”
Section: Introductionmentioning
confidence: 98%
“…HRM in healthcare: the role of work engagement job resource because it reduces the effect of job demands. Beh and Loo (2012) and Appelbaum and Gandell (2003) concluded that healthcare workers become disillusioned and stressed from their work when they are not provided with sufficient and timely communication. This sense of disengagement is then likely to result in lower levels of quality and safety.…”
mentioning
confidence: 99%